2011
DOI: 10.1111/j.1813-6982.2011.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Uncertainty and Conditional Stock Market Volatility in South Africa*

Abstract: This paper analyses how systematic risk emanating from the macroeconomy is transmitted into stock market volatility using augmented autoregressive Generalised Autoregressive Conditional Heteroscedastic (AR‐GARCH) and vector autoregression (VAR) models. Also examined is whether the relationship between the two is bidirectional. By imposing dummies for the 1997‐1998 Asian and the 2007‐2009 sub‐prime financial crises, the study further analyses whether financial crises affect the relationship between macroeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 54 publications
9
84
0
2
Order By: Relevance
“…Furthermore, the use of monthly data is in accordance with strong financial literature (e.g. see Bloom, 2009;Braun, Nelson, & Sunier, 1995;Chinzara, 2011;Doukas, Hall, & Lang, 2003;Faff & Brailsford, 1999;Hansson & Hordahl, 1998;Khan, Muneer, & Anuar, 2013;Lanne & Luoto, 2008;Manolis, Stelios, & Angelos, 2002;Sadorsky, 2001 andWest &Worthington, 2006). Then, as is practice in the financial literature, the return series will be expressed in logarithmic difference between the two successive prices acquiring the continuous compounding returns (i.e.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the use of monthly data is in accordance with strong financial literature (e.g. see Bloom, 2009;Braun, Nelson, & Sunier, 1995;Chinzara, 2011;Doukas, Hall, & Lang, 2003;Faff & Brailsford, 1999;Hansson & Hordahl, 1998;Khan, Muneer, & Anuar, 2013;Lanne & Luoto, 2008;Manolis, Stelios, & Angelos, 2002;Sadorsky, 2001 andWest &Worthington, 2006). Then, as is practice in the financial literature, the return series will be expressed in logarithmic difference between the two successive prices acquiring the continuous compounding returns (i.e.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…In this Generalised ARCH model, he sets the current conditional variance as a function of the previous square error term and past conditional variance. It is indeed incredible that this one GARCH (1, 1) model can be sufficiently applied in any financial time series in order to comprehend the volatility dynamics (for example, see Chinzara, 2011;Engle, 2004 andElyasiani et al, 2011). Following the strong financial literature (see, for example, Chinzara, 2011;Engle, 2004;Elyasiani et al, 2011 andGoudarzi &Ramanarayanan, 2010), this research study also applied GARCH (1, 1) to estimate various volatility dynamics.…”
Section: Garch (1 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…They have recapitulated that macroeconomic volatility significantly causes stock market volatility. However, Oseni and Nwosa (2011) have not found any evidence on the causal relationship between stock market volatility and the volatility in interest rate and inflation rate but Chinzara (2011) have found that macroeconomic uncertainty significantly affects stock market volatility (See also: Okoli, 2012). Kadir et al (2011) have examined the impact of interest rate volatility and exchange rate volatility on stock return volatility.…”
mentioning
confidence: 99%